Peran dan Strategi SMAS Adabiah 2 Padang dalam Penguatan Kompetensi Siswa Berprestasi Unggul - Rahmi Juwita; Piki Sentri Pernantah (Kilau Publishing, 2025)
This study aims to analyze the role and strategies of SMAS Adabiah 2 Padang in strengthening student competencies in both academic and non-academic domains. The school is recognized as one of the leading private secondary schools in Padang, known for its various achievements. Employing a qualitative approach with a case study method, data were collected through interviews, observations, and documentation. The findings reveal that the enhancement of student competencies is implemented systematically through strong leadership, structured development regulations, interest- and talent-based training, and adequate facility support. Collaboration among school leaders, teachers, extracurricular coaches, and education staff is a key factor in the success of these strategies. Student achievement has shown an upward trend from 2023 to 2025. However, this study is limited by its time frame and single-case scope. The results contribute to the development of performance-based school management. Recommendations are directed toward strengthening digital systems, supporting infrastructure, and developing a sustainable coaching model.